SOSIALISASI TERAPI EMOTIONAL FREEDOM TECHNIQUE (EFT) UNTUK MENURUNKAN SKALA NYERI PADA PASIEN DYSPEPSIA DI RUANG IGD RSUD KARAWANG - Yumi Dian Lestari; Wirdan Fauzi Rahman; Tiara Puspita (Bajang Institute, 2025)
Dyspepsia is a digestive disorder that often causes pain in the pit of the stomach. Emotional Freedom Technique (EFT) is a non-pharmacological therapy method carried out by tapping certain points on the body while making positive affirmations, aimed at reducing stress levels and pain perception. Socialization and training to improve nurses' abilities in dealing with emergency situations in addition to pharmacological therapy. This community service activity aims to improve the knowledge and skills of nurses in the Emergency Room of Karawang Regional Hospital in performing emotional freedom technique (EFT) therapy to reduce the pain scale in dyspepsia patients in the Emergency Room of Karawang Regional Hospital. The implementation method used a lecture, demonstration, and simulation approach. The activity involved 20 participants consisting of implementing nurses and shift managers. Evaluation was carried out using pre-tests and post-tests to assess knowledge gains, as well as observation of skills during the simulation practice. The results of the activity showed an increase in participants' knowledge from an average of 58% (pre-test) to 89% (post-test). In addition, 90% of participants were able to perform the EFT therapy simulation with the correct technique. Participants also demonstrated high enthusiasm throughout the series of activities. The socialization and training on EFT therapy proved effective in improving the knowledge and skills of nurses at Karawang Regional Hospital. It is hoped that this activity can be implemented continuously to develop emergency response nurses. EFT therapy has been shown to be effective in reducing pain levels in dyspepsia patients and can be used as an alternative non-pharmacological intervention for pain management in the emergency department